Antenatal exposure to e-cigarette vapor as a possible etiology to total colonic necrotizing enterocolitits: A case report - Sarah Gillen; Daniel Saltzman (Journal of Pediatric Surgery Case Reports, 2014)
Antenatal exposure to cigarette smoke is associated with preterm births, low birth weights, and pediatric lung disease. This case report is the first documented potential adverse effect e-cigarettes to a fetus.